UPAYA MEMENUHI KEBUTUHAN BAHAN BAKU YANG SESUAI DENGAN RENCANA PRODUKSI MELALUI PENYUSUNAN ANGGARAN (STUDI KASUS PADA ADI SASIRANGAN BANJARMASIN) - Widya Ais Sahla; Recha Rahmadhana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,The purpose of this study is to calculate the budget of the raw material in Ady Sasirangan Banjarmasin on 2017. During this time the company has never made the planning of the production process and raw material purchases so it can not determine how the purposes of the raw materials required for the production process in a year.The research method of case study approach is to compare the calculation of sales budget with approach of the three methods of Least Square method, Moment method, and Quadrat method then calculated based on Standard Forecasting Error (SKF) to determine the most appropriate. The third method method by taking the smallest end value. Further predicted the production is based on previous years and calculate the raw material budget in the production of one year.The research results can be concluded from the calculation of the value of Standar Kesalahan Forecasting (SKF) the most appropriate method used is the Least Square method and Moment method for Silk Sasirangan and Kuadrat method for Cotton Sasirangan because it has the smallest SKF value and close to the suitability. In the calculation of the budget of the use of raw materials in 2017 is for Silk Sasirangan cloth of 7.309 meters of plain fabric, 1.096 ounces dye powder, 1.096 ounces napthol, 1.096 ounces indantherene, 3.655 roll of yarn. For Cotton Sasirangan as much as 390 ounces of plain fabric, 590 oz dye powder, 590 ounce napthol, 590 ounce indantherene, 1.965 roll of yarn. While the calculation of raw material purchase budget is Rp 160.803.588 for silk plain cloth, Rp 53.055.000 for cotton plain fabric, Rp 12.644.161 for dye powder, Rp 12.644.161 for napthol, Rp 45.518.979 for indantherene and Rp 33,717,762 for the yarn.